2023
DOI: 10.1111/bcp.15799
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual abnormalities after COVID‐19 vaccination in the Netherlands: A description of spontaneous and longitudinal patient‐reported data

Abstract: AimsDuring the COVID‐19 vaccination campaigns, the number of reports of menstrual abnormalities increased rapidly. Here, we describe the nature and potential risk factors associated with menstrual abnormalities based on spontaneously reporting data as well as data from a prospective cohort event monitoring (CEM) study as these are poorly studied.MethodsReports of menstrual abnormalities received by the Netherlands Pharmacovigilance Centre Lareb in the spontaneous reporting system between February 2021 and Apri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Bisgaard Jensen et al mentioned that change in menstrual cycle length was the most frequently reported change (9% longer menstrual cycles and 7% shorter menstrual cycles (Bisgaard Jensen et al, 2023). In the study by Duijster et al, amenorrhoea/ oligomenorrhoea was also the most reported menstrual outcome (33% of 24,090 spontaneous reports) (Duijster et al, 2023). Caspersen et al found a longer interval in girls aged 12-15 years (RR = 1.15, 95%CI 1.05-1.27), and in girls aged 14-15 years (RR = 1.17, 95%CI 1.05-1.31).…”
Section: Covid-19 Vaccination and Menstrual Cycle Lengthmentioning
confidence: 98%
See 4 more Smart Citations
“…Bisgaard Jensen et al mentioned that change in menstrual cycle length was the most frequently reported change (9% longer menstrual cycles and 7% shorter menstrual cycles (Bisgaard Jensen et al, 2023). In the study by Duijster et al, amenorrhoea/ oligomenorrhoea was also the most reported menstrual outcome (33% of 24,090 spontaneous reports) (Duijster et al, 2023). Caspersen et al found a longer interval in girls aged 12-15 years (RR = 1.15, 95%CI 1.05-1.27), and in girls aged 14-15 years (RR = 1.17, 95%CI 1.05-1.31).…”
Section: Covid-19 Vaccination and Menstrual Cycle Lengthmentioning
confidence: 98%
“…Different results were found regarding menstrual disorders after specific COVID-19 vaccine brands. Some studies did not find differences between the vaccine brands AstraZeneca, Johnson & Johnson, Moderna, and Pfizer (Alvergne et al, 2022;Muhaidat et al, 2022;Qashqari et al, 2022;Rogers et al, 2022;Alvergne et al, 2023b;Darney et al, 2023;Saleh Alzahrani et al, 2023;Wali et al, 2023), whereas others found that Pfizer (Wong et al, 2022;Al-Furaydi et al, 2023;Duijster et al, 2023;Filfilan et al, 2023), Moderna (Alahmadi et al, 2022;Trogstad et al, 2023), or AstraZeneca (Filfilan et al, 2023) resulted in a higher rate of menstrual changes compared to other COVID-19 vaccines.…”
Section: Literature Searchmentioning
confidence: 99%
See 3 more Smart Citations